Unequal exchange? recent transfers of agricultural resources and their implications for developing countries - Fowler, Cary; Smale, Melinda; Gaiji, Samy (Wiley, 2001)
Plant genetic resources constitute the biological basis for plant breeding and future agricultural development. Their transfer from developing to developed countries over centuries has sometimes been viewed as an example of exploitation, if not ‘biopiracy’. Modern gene flows are different in character and magnitude from historic exchanges, however. This article examines current patterns and finds that developing countries are major net recipients of germplasm samples from CGIAR centres, particularly if ‘improved materials’ are considered. Potentially problematic, intellectual property rights do not currently present major barriers to the availability and use of genetic resources by developing countries. Proposals to restrict flows and redress perceived injustices may reduce the benefits accruing at present to developing countries from germplasm exchanges.